Misconceptions of High School Students in Salt Hydrolysis Topic Using a Three-Tier Diagnostic Test (TTDT) - Tri Prianti; Elfi Susanti VH; Nurma Yunita Indriyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2020)
This study aims to find out whether high school students in Surakarta have misconceptions in salt hydrolysis material and to find out which concept is the most misconception experienced by high school students in Surakarta in salt hydrolysis material. This study used a descriptive approach. Data collection techniques using data triangulation technique from the results of the Three-Tier Diagnostic Test (TTDT), formative tests, and interviews. The sample used in this study was determined using a purposive sampling technique. Based on the research conducted, high school students in Surakarta experienced misconceptions in salt hydrolysis material as much as 36.75%, 35.94% Scientific knowledge, 15.63% lack of knowledge, and 10.90% error. Most misconceptions experienced by high school students in Surakarta on salt hydrolysis material occur in sub concepts: a) conclude the acid-base properties shown from salt solutions (49.91%), b) calculate the pH of the salt solution (39.15), c) analyze the reaction salt hydrolysis (37.21%), d) analyze the concept of hydrolysis that occurs in solution (35.98), e) determine the types of hydrolysis of salt (21.87%).